Sideritis perfoliata Ethanolic Extract Mitigates Acetic Acid-Induced Ulcerative Colitis in Rats - Dilek Özbeyli; Ali Şen; Naziye Özkan Yena; Ayşe Nur Hazar Yavuz; Deniz Mukaddes Türet; Meral Yüksel; Leyla Bitiş; Ahmet Doğan; Aslı Aykaç (European Journal of Biology)
Objective: This study evaluated the antioxidant and anti-inflammatory effects of Sideritis perfoliata (SP) ethanolic extract in vitro and its impact on anti-inflammatory, antiapoptotic, oxidative stress, and tissue damage-related parameters in an ulcerative colitis (UC) rat model.Materials and Methods: Dried and ground aerial parts of SP were extracted with 90% ethanol using maceration. Then, the SP extract’s radical scavenging, anti-5-lipoxygenase (LOX) activities, and total secondary metabolic quantities were evaluated in vitro. In in vivo experiments, following acetic acid (AA)-induced colitis, physiological saline (PS) (1 mL, og), sulfasalazine (SS) (100 mg/kg bwt, 1mL, og), and SP extract (200 mg/kg bwt, 1mL, og) treatments were administered to AA, SS, and SP groups, respectively, once daily for three consecutive days. PS was given to the control group. At the 72nd hour, the rats were euthanized. Analyses were performed on colon tissues using ELISA, Chemiluminescence assay, Haematoxylin and Eosin staining.Results: SP extract exhibited good antioxidant activity against 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and strong anti-5-LOX activity. The total amounts of phenol, flavonoid, and triterpene compounds in the extract were determined. Compared with the AA group, SS or SP extract treatments reduced tumour necrosis factor-α, interleukin-1β, interleukin-17, tool-like receptor-9, matrix metalloproteinases-3, caspase-9, caspase-3, luminol, and lucigenin chemiluminescence levels, macroscopic and microscopic morphological scores in colon. Conclusion: Due to its flavonoids, phenolic acids, triterpene content, anti-5-LOX, and free radical scavenging activities, SP extract attenuates proinflammatory cytokines, mitochondrial apoptotic caspases, and oxidative stress. Our findings support the ethnopharmacological use of SP for colitis.